Drone Warfare in the Mirror of Human Rights - Perger, Adam (Nurani Hukum, 2024)
International humanitarian law is divided into two main "branches": jus in bello and jus ad bellum. The jus ad bellum is the branch of international humanitarian law that deals with the rules that govern the justification of the use of force by states, for example, the question of whether a war is defensible; historically, it was the analysis that formed the basis of the just war theory. Today, Article 51 of the UN Charter reflects a recognized jus ad bellum justification in the form of self-defense; other similar justifications, such as those based on the responsibility to protect and humanitarian intervention, have still not acquired the status of customary international law. The traditional distinction between the two bodies of international humanitarian law entails that warfare, governed by the principles of military necessity, is a distinction between proportionality and humanity (jus in bello), separated from reasons and legal justification (jus ad bellum). However, such distinctions between these two categories of law in armed conflict are increasingly arbitrary and outdated, and the justification of the use of drones in humanitarian law terms further complicates the situation